A Competence of Teacher in Making e-LKPD Using Flip Book Maker with Emphasis on Macro, Submicro, and Simbolic Level Representation of Chemistry - Miftahul Khair; Minda Azhar; Alizar Ulianus (Pelita Eksakta, 2020)
The aim of the Community Partnership Program (PKM) service activity is to increase teacher competency in making electronic electronic Student Work Sheets (e-LPKD) using flip book makers with an emphasis on three levels of chemical representation. The method used is lectures, demonstrations and workshops. The lecture and demonstration methods are used to deliver the topics i.e ICT and internet terminology, industrial revolution 4 and three levels of chemical representation. The practice includes quick tricks of editing images from general chemistry books and transferring them to LKPD. Workshops are to make e-LKPD using a flip book maker accompanied by videos of learning chemistry, animation of chemical concepts. This activity can improve the knowledge and skills of chemistry teachers using standard general chemistry e-books, videos of chemistry learning and chemical animation from internet. This community service activities can improve the knowledge and skills of chemistry teachers in integrating a variety of learning resources that can be used to create ICT-based e-LKPD by emphasizing on three levels of chemical representation.